Crossing Borders, Opening Minds? VET Tandem Partnerships in a Dutch- German Cross-Border Region - Wilde, Stephanie; Kremer, Hugo; Stelzer, Jana (International Journal for Research in Vocational Education and Training, 2025)
Purpose: The purpose of this paper is to discuss the potential contribution of cross-border vocational education and training (VET) exchange partnerships within the context of tandem exchanges between VET institutions in the Rhine-Waal Euregio region in the Netherlands and Germany. These tandem exchanges offer learners and teachers in VET the opportunity to develop new perspectives on their training pathways, the labour market and learning approaches in each context respectively. This occurs through the discussion and debate ignited by the exchanges, as well as through visits to relevant VET institutions, companies and other institutions in the border region. Approach: The approach taken in the paper uses both documentary analysis of a long-standing cross-border VET network, Ler(n)ende Euregio, as well as an interview-based study. Group interviews were held with teachers and school leadership teams from three tandem partnerships in North-Rhine Westphalia and the Netherlands, namely in the Rhine-Waal border region. The interviews revealed aspects of the motivation for the tandems and the challenges involved. Findings: The findings showed that learning opportunities for the students and the teachers are considerable and include: Gaining an insight into their vocational training pathway in the neighbouring country, and thereby reflecting on their own VET experience; developing social, intercultural and linguistic competences. This occurs particularly because of the switch between host and guest modes. Further, such exchanges can play a role in tackling prejudice in both cross-border contexts. Challenges faced by the tandem partnerships include: Maintaining continuity in the participating VET institutions and the teachers responsible for the exchanges and overcoming logistical and bureaucratic hurdles. Greater recognition of cross-border exchanges through certification for learners and dedicated time on the curriculum could be positive steps. Conclusion: The paper concludes that tandem partnerships in the Dutch-German border region offer a sustainable and accessible addition to the palette of mobilities available to learners and, significantly, also to teachers, in VET. The potential, particularly for learners who may not otherwise travel abroad during their training, is considerable, and is arguably relevant to other cross-border regions and international contexts.